Advantages and problems with pregnancy registries: observations and surprises throughout the life of the International Lamotrigine Pregnancy Registry‡. (27th June 2014) - Sinclair, Susan; Cunnington, Marianne; Messenheimer, John; Weil, John; Cragan, Janet; Lowensohn, Richard; Yerby, Mark; Tennis, Patricia
ABSTRACT Purpose The International Lamotrigine Pregnancy Registry monitored for a signal of a substantial increase in the frequency of major congenital malformations associated with lamotrigine exposures in pregnancy over an 18‐year period. Key methodological lessons are discussed. Methods The strengths and weaknesses of the Registry were assessed using quantifiable methodological and operational parameters including enrollment, completeness of exposure and outcome data reporting, and lost to follow‐up. The choice of comparator groups and stopping rules for registry closure were critically evaluated. Results The reliance on voluntary reporting was associated with a clustered geographical distribution of registered pregnancies. The enrollment rate increased over time with new approvals and indications for lamotrigine and publication of interim data. Reporter burden was minimized through a streamlined data collection approach resulting in a high level of completeness of exposure and primary outcome data. Lost to follow‐up rates were high (28.5% overall) representing a major limitation; incentives to increase the completeness of reporting failed to reduce rates. A lack of an internal comparator group complicated data interpretation; but external comparisons with multiple external groups allowed an assessment of consistency of outcome data across multiple data sources. A lack of a priori closure criteria prolonged the life of the Registry, and consideration of regulatory guidelines on this subject is encouraged at the time of conception of future registries. Conclusions A successful pregnancy exposure registry requires ongoing flexibility and continuous re‐assessment of enrollment, recruitment, and retention methods and the availability of comparison data, throughout its lifecycle. Copyright © 2014 John Wiley & Sons, Ltd.